2016
DOI: 10.1007/s11096-016-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived needs of pharmaceutical care services among healthcare professionals in South Korea: a qualitative study

Abstract: Purpose To explore the need for pharmaceutical care services, key features of desirable pharmacy services, and perceived barriers for advancing the services in hospital environments with doctors and nurses who are key co-workers of the interdisciplinary team care services.Methods Semi-structured, in-depth interviews with eighteen doctors and fifteen nurses employing purposive and snowballing sampling strategies were conducted in ten hospitals in South Korea. Results The level of pharmaceutical care was varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…This descriptive study demonstrated that clinical pharmacists' collaboration with physicians and nurses in hospital increased patient safety and improved the quality of prescribing and that doctors perceived this collaboration as beneficial both for themselves and their patients [23]. In a study, from South Korea, the nurses interviewed discussed the need for pharmacists in improving communication, drug counselling, providing information about drug distribution in the market, implementing an easy-to-use drug identification system, providing a medication reconciliation service and providing education to nurses about medications [25]. In the study by Salgado et al, nurses from Australia and Portugal were interviewed and whilst Australian nurses were aware of the clinical competencies of pharmacists, in contrast, Portuguese nurses appeared to have little knowledge of pharmacists competencies [26].…”
Section: Introductionmentioning
confidence: 99%
“…This descriptive study demonstrated that clinical pharmacists' collaboration with physicians and nurses in hospital increased patient safety and improved the quality of prescribing and that doctors perceived this collaboration as beneficial both for themselves and their patients [23]. In a study, from South Korea, the nurses interviewed discussed the need for pharmacists in improving communication, drug counselling, providing information about drug distribution in the market, implementing an easy-to-use drug identification system, providing a medication reconciliation service and providing education to nurses about medications [25]. In the study by Salgado et al, nurses from Australia and Portugal were interviewed and whilst Australian nurses were aware of the clinical competencies of pharmacists, in contrast, Portuguese nurses appeared to have little knowledge of pharmacists competencies [26].…”
Section: Introductionmentioning
confidence: 99%
“…The “customer journey maps” allowed us to see which parts of the service might need improvement ( Fig 2 ) [ 16 ]. Finally, we conducted focus group discussions and in-depth interviews with 18 physicians and 15 nurses to gather information about their interests and discomfort in current services, as well as their expectations for new MTC services [ 10 ]. We also completed face-to-face surveys with 219 patients and focused on identifying their needs for improved MTC services [ 10 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in South Korea, the development of MTC service is in the beginning stages, and healthcare professionals still independently provide services to patients. Furthermore, services in hospital pharmacies are limited to medication counseling, anticoagulation counseling, therapeutic drug monitoring, and similar services, despite the high risk of medication-related problems [ 10 ]. For this reason, advanced pharmaceutical care services for patients who may have medication-related problems are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…We previously published the qualitative analyses of the PCS needs by health care providers and this study focused on PCSs with patients’ perspectives. 21 …”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was preformulated by facts clustering, opportunity web, and mind map processes so that various matrices of PCSs could be completed. 21 The prototype questionnaire had consisted of eleven satisfaction and eleven expressed needs. We held focus group discussions with clinical pharmacists with PCSs experiences and pharmacy school faculties, and conducted focused individual interviews with physician specialists and registered nurses.…”
Section: Methodsmentioning
confidence: 99%